Comparative Evaluation of Gingival Healing Following Gingivectomy Using Grapeseed Extract Gel and Amla Gel: A Clinical Study - Bodduru, Ruparani; kanakagiri, Phani Yasaswini; Nikitha, Erva; N, Swetha.; Rajaram, Haripriya; Mrunalini, K.V.Sai (Journal of Neonatal Surgery, 2025)
Objective: To assess and compare the clinical efficacy of grapeseed extract gel and amla gel in promoting gingival healing post-gingivectomy Methods: A randomized clinical trial was performed on a group of 20 patients scheduled for gingivectomy. Participants were assigned to two groups: Group A (10 patients) received topical grapeseed extract gel, and Group B (10 patients) received amla gel after ginigivectomy procedure. Clinical parameters including Gingival Index (GI), Wound Healing Index (WHI) were assessed at DAY 10, DAY 20 and DAY 30 postoperatively. Pain assessment was carried out using the Visual Analog Scale (VAS) at 24 and 72 hours, as well as on the 10th, 20th, and 30th day after the surgery. Results: Both groups exhibited significant decreases in gingival inflammation over the follow-up period (Group A: GI from 2.00 to 0.43; Group B: 2.00 to 0.86; p < 0.05). Wound healing progressed in both groups, with Group A showing a higher mean WHI at Day 30 (3.60 vs. 3.20), though the difference was not statistically significant (p = 0.075). Pain levels declined significantly in both groups from 24 hours (mean VAS 4.50) to Day 30 (0.00), without significant differences between the groups at any evaluated time (p > 0.05). Conclusion: Grape seed extract gel appears to enhance wound healing and reduce gingival inflammation more effectively than amla gel after gingivectomy, while both treatments provide comparable postoperative pain relief. These gels serve as effective adjuncts in improving clinical outcomes following gingival surgery.